Post-treatment effect of sodium and dodescyl sulphate-triethanolamine on the in vitro dry matter digestibility estimation of tanniferous tree leaves using polyethylene glycol-6000 - Vaithiyanathan, S; Mishra, J P; Jakhmola, R C (The Indian Journal of Animal Sciences, 2005)
The aim of the present experiment was to find out effect of sodium dodecyl sulphate (SDS)-triethanolamine (TE) addition at the end of the incubation period on in vitro dry matter digestibility (IVDMD) of young and mature leaves of tanminiferous trees (Bauhinian racemosa, Dicrostachhys nutans, Ficus bengalensis, F religiosa, Gymnosporia spinosa, Prosopis cineraria and Zizyphus mamularia) treated with polyethylene glycol (PEG)-6000. Most of young leaves had higher amount of condensed tannin (CT) (ranging from 1.03 to 13.13% DM) than in mature leaves (ranging from 0.31 to 14.0% DM). The IVDMD ranged from 25.33 to 66.27 and 18.40 to 36.47%, respectively, for young and mature leaves. CT had significantly (P